An Implementation Iot Weather Station Based On ESP 32 - Beni Satria; Rahmaniar, Rahmaniar; M. Erpandi Dalimunthe (Jurnal Scientia, 2024)
This study discusses the development of an Internet of Things (IoT)-based weather station using NodeMCU ESP32, BMP280 sensor, and DHT11. This weather station is designed to collect real-time temperature, humidity, and atmospheric pressure data, and transmit them to an online platform for further analysis. NodeMCU ESP32 is used as the main microcontroller tasked with controlling and collecting data from both sensors. The BMP280 sensor is used to measure atmospheric pressure and temperature, while the DHT11 sensor is used to measure air humidity. The collected data is sent via a Wi-Fi connection to the Blynk server for storage and analysis. Through the use of IoT technology, this weather station provides the ability to monitor weather conditions in real time and take necessary actions based on the collected data. Integration with an online platform allows remote data access, allowing users to monitor weather conditions from anywhere. Thus, this study not only illustrates the implementation of IoT technology in monitoring weather but also opens up opportunities for broader applications in environmental monitoring and resource management.